2020
DOI: 10.1016/j.annemergmed.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Mortality of Patients After Emergency Department Treatment for Nonfatal Opioid Overdose

Abstract: Twitter: @scottweinermd.Study objective: Despite the increased availability of naloxone, death rates from opioid overdose continue to increase. The goal of this study is to determine the 1-year mortality of patients who were treated for a nonfatal opioid overdose in Massachusetts emergency departments (EDs). Methods:This was a retrospective observational study of patients from 3 linked statewide Massachusetts data sets: a master demographics list, an acute care hospital case-mix database, and death records. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 2 publications
3
120
1
Order By: Relevance
“…The incidence of all-cause mortality at 1 year in our study (5.3%) was lower than in 2 previous studies conducted within a US health care plan, 16,17 and similar to that in a recent statewide study in Massachusetts. 23 The rate of opioid-related mortality is higher in the United States than in Canada, which may contribute to differences compared with our study findings. 4,24 However, the variation between studies in the United States may be due to different methods in assessing the outcome.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The incidence of all-cause mortality at 1 year in our study (5.3%) was lower than in 2 previous studies conducted within a US health care plan, 16,17 and similar to that in a recent statewide study in Massachusetts. 23 The rate of opioid-related mortality is higher in the United States than in Canada, which may contribute to differences compared with our study findings. 4,24 However, the variation between studies in the United States may be due to different methods in assessing the outcome.…”
Section: Discussioncontrasting
confidence: 83%
“…The study in Massachusetts could have produced a lower estimate because of challenges with data linkage. 23 As in the previous US health care plan study, we found an increased risk for all-cause mortality among patients with benzodiazepine use. 16 We found discordant results, with an association between mental health and substance-use-related diagnoses and lower all-cause mortality, but higher opioid-related mortality for individuals prescribed opioid agonist therapy.…”
Section: Discussionsupporting
confidence: 76%
“…A survey by the American College of Emergency Physicians/Morning Consult discovered that 80% of individuals surveyed were concerned about contracting COVID-19 from another patient or visitor if they needed to go to the emergency department (17). While the initial mortality of patients who refuse transport immediately after naloxone reversal is low (18), this increase in refusal rate is nevertheless concerning, and the one-year mortality of individuals who survive an opioid overdose is quite high (19,20). In part to address this concern, Massachusetts implemented an EMS protocol for "Leave-Behind Naloxone", in which when a patient refuses transport, the patient and/or an accompanying individual can be given a naloxone kit and instructed on its use (21).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Also, there was a 30% increase in ED visits for opioid overdose between 2016 and 2017 [6]. Of 11,557 ED patients in Massachusetts who were treated for a non-fatal opioid overdose, 5.5% died within 1 year, 1.1% within 1 month, and 0.25% within 2 days [7]. As such, patients discharged from the ED following a non-fatal opioid overdose face a high short-term risk of death.…”
Section: Introductionmentioning
confidence: 99%